Transformative Learning Strategies for Effective Teaching and Learning in Digitized Higher Education - Fareeha Javed (Jurnal Pendidikan, 2024)
Higher education is experiencing a shift at a rate never previously seen owing to a change in higher education theory and practices that have become more learner-centered globally. As the value of higher education has increased, education has also become an ongoing activity. Transformative learning theory is widely used in higher education because it provides advice on how people might discover meaning in their lives. Teachers can improve their theory and practice of instruction through transformational learning by critically assessing and revising their assumptions and expectations to promote higher education students’ successful learning. Higher education institutions are finding it increasingly difficult to adapt to changing facilities brought about by digitization, technological innovations, increased technological connectivity, workplace diversity, mobility and migration, and global market expansion. This paper delves deeply into the concepts of digital transformation and transformational learning practices in order to help readers understand their importance and function in effective teaching and learning in transforming higher education. The primary contribution of this paper is the delivery of transformative learning strategies and a comprehensive approach on how to effectively integrate digital technologies into the teaching and learning process to increase student engagement, knowledge retention, and the development of critical thinking skills.